Antimicrobial potential of selected plant extracts against important plant pathogenic microorganisms - PUTTASWAMY RAJESHWARI; KOTESHWASR ANANDRAO RAVEESHA (International Journal of Pharma and Bio Sciences, 2017)
Evaluation of natural products as safe and effective antimicrobial agents is one of the scientific strategies to combat the menace of drug-resistance and pesticide pollution. Aqueous extract and different solvent extracts of seeds of Trachyspermum ammi, leaves of Murraya koenigii (Linn.) Spreng., peels of Cucumis sativus Linn. and Citrullus lanatus Thunb., were screened in vitro for antimicrobial activity against phytopathogenic microbes namely, Xanthomonas axonopodis pv. vesicatoria, Xanthomonas campestris pv. campestris, Pseudomonas syringae, Aspergillus flavus and Fusarium verticelloides by agar cup diffusion method. Among the aqueous and different solvent extracts, methanol extract of M. koenigii showed significant activity against all the tested bacteria and F. verticelloides (zone of inhibition ranged from 8 to 53 mm).Methanol extracts of C. sativus recorded an inhibition zone of 15 mm against X. a. pv. vesicatoria and13mm against X. c. pv. campestris. Chloroform, ethyl acetate and methanol extracts of T. ammi recorded zone of inhibition ranging from 8 to 32mm against all the test bacteria and F. verticelloides. The antimicrobial activity of these promising plant extracts when compared with standard drugs streptocycline, bacteromycin and bavistin revealed significant inhibitory potential. Preliminary phytochemical analysis of the active extracts revealed the presence of tannin in all the tested extracts. The positive results of the present evaluation provide primary platform for further pharmacological studies.